Fecal microbiota and diets of muskox female adults and calves. Issue 5 (3rd May 2022) - Cheon, Ji‐Yeon; Cho, Hyunjun; Kim, Mincheol; Park, Hyun Je; Park, Tae‐Yoon S.; Lee, Won Young
Abstract: In mammals, the gut microbiome is vertically transmitted during maternal lactation at birth. In this study, we investigated the gut microbiome and diets of muskox, a large herbivore inhabiting in the high Arctic. We compared the microbiota composition using bacterial 16S rRNA gene sequencing and diets using stable isotope analysis of muskox feces of six female adults and four calves on Ella Island, East Greenland. Firmicutes were the most abundant bacterial phylum in both the adults and calves, comprising 94.36% and 94.03%, respectively. Significant differences were observed in the relative abundance of the two Firmicutes families. The adults were primarily dominated by Ruminococcaceae (73.90%), and the calves were dominated by both Ruminococcaceae (56.25%) and Lachnospiraceae (24.00%). Stable isotope analysis of the feces in the study area revealed that both adults and calves had similar ranges of 13 C and 15 N, likely derived from the dominant diet plants. Despite their similar diets, the different gut microbiome compositions in muskox adults and calves indicate that the gut microbiome of the calves may not be fully colonized to the extent of that of the adults. Abstract : We present fecal microbiota and diet compositions of muskox female adults and calves in northeast Greenland. By 16S sequencing and stable isotope analysis, we found that the mother and calf have different microbial communities despite the similar diet. We discuss that the gut microbiome of the calves may not be fully colonized yet as much as one of the adults.